2022
DOI: 10.3389/fpls.2022.906725
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Characteristics and Phylogenetic Analysis of the Artemisia argyi Chloroplast Genome

Abstract: Artemisia argyi Levl. et Van is an important Asteraceae species with a high medicinal value. There are abundant A. argyi germplasm resources in Asia, especially in China, but the evolutionary relationships of these varieties and the systematic localization of A. argyi in the family Asteraceae are still unclear. In this study, the chloroplast (cp) genomes of 72 A. argyi varieties were systematically analyzed. The 72 varieties originated from 47 regions in China at different longitudes, latitudes and altitudes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…This phenomenon might be explained by the fact that the geographical area of origin might influence the variation of I. rubescens. Another previous study supported the same conclusion; the Artemisia argyi collected from different geographical areas display high intraspecific diversity in the cp genome (Chen et al, 2022). In addition, clade B only includes a species of I. ternifolious, which was supported by the findings of other researchers based on trnD-trnT, psbA-trnH, rpl32-trnL, trnL-trnF, rps16, and nrITS (Zhong et al, 2010;Yu et al, 2014;Chen et al, 2021).…”
Section: Species Identification and Phylogenetic Analysissupporting
confidence: 73%
“…This phenomenon might be explained by the fact that the geographical area of origin might influence the variation of I. rubescens. Another previous study supported the same conclusion; the Artemisia argyi collected from different geographical areas display high intraspecific diversity in the cp genome (Chen et al, 2022). In addition, clade B only includes a species of I. ternifolious, which was supported by the findings of other researchers based on trnD-trnT, psbA-trnH, rpl32-trnL, trnL-trnF, rps16, and nrITS (Zhong et al, 2010;Yu et al, 2014;Chen et al, 2021).…”
Section: Species Identification and Phylogenetic Analysissupporting
confidence: 73%
“…Contraction and expansion of the IR/SC region boundaries are the main reason for changes in chloroplast genome length, playing a vital role in its evolution. These boundaries can be used to study species-specific gene loci (Gui et al 2020), and previous studies found that the IR/LSC and IR/SSC junctions vary among Artemisia species (Chen et al 2022). Here, we found only slight differences in IR boundaries between the nine Artemisia species, indicating these species are closely related.…”
Section: Discussionsupporting
confidence: 48%
“…The cp genomes of five Artemisia species contain 114 genes, which was similar to those of Artemisia annua ( Shen et al., 2017 ). Like most other Artemisia species, ycf1 and rps19 were also detected, but the copy number and location were different, ycf1 spans the IRb/SSC boundary, this was also seen in A. scoparia and A. absinthium ( Chen et al., 2022 ). The GC content of the IR region was significantly greater than that of the LSC and SSC regions.…”
Section: Discussionmentioning
confidence: 90%
“…species, ycf1 and rps19 were also detected, but the copy number and location were different, ycf1 spans the IRb/SSC boundary, this was also seen in A. scoparia and A. absinthium (Chen et al, 2022). The GC content of the IR region was significantly greater than that of the LSC and SSC regions.…”
Section: Figurementioning
confidence: 93%